THE FUTURE OF E-ARBITRATION IN MALAYSIA: PRELIMINARY ANALYSIS ON THE LEGITIMACY OF E-ARBITRAL AGREEMENT AND PROCEDURES (UUM Journal of Legal Studies, 2022)
Using electronic technology in the dispute resolution industry has been encouraged globally. Electronic arbitration (e-arbitration) is one of the main online dispute resolution mechanisms, and it should be implemented in Malaysia because of its significant advantages. Unfortunately, the future of e-arbitration in Malaysia is still hazy. Therefore, it is important to examine whether existing Malaysian laws are sufficient to legalise the e-arbitral agreement and e-arbitral proceedings. This article is based on a research carried out for a doctoral degree. Primary and secondary sources were consulted. The novelty of the contribution has provided legal evidence and arguments that the relevant laws in Malaysia were to some extent, modern and advanced to recognise e-arbitration. However, from a purely legal perspective, several gaps should be appropriately addressed by Malaysian lawmakers in order to ensure the sustainable and successful establishment of e-arbitration in the country.